Perancangan Sistem Informasi Pembelian Bahan Baku Dengan Object Oriented Methodology - Rahayu, Sri; Armeita, Adinda Adisty; Setiawan, Nursita (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2023)
The technology-based information system used in the company is very helpful and facilitates work productivity in each company. However, there are still some companies that have not used computerized systems properly. One of them is at PT. Pilar Makmur Utama. There are obstacles in the purchasing process and the slowness of ordering because the admin has to manually calculate raw materials, as well as the frequent loss and scattering of supplier receipts, making it difficult to make reports every month. For this reason, an information system is needed, so that it will facilitate the search for data and the recording process. This system is designed using Unified Modeling Language modeling. So with this system, the problem at PT. The Main Makmur Pillar can be handled properly and help the company's performance to be more effective according to user needs.